1997
DOI: 10.1007/s11626-997-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

GTSF-2: A new, versatile cell culture medium for diverse normal and transformed mammalian cells

Abstract: The aim of this study was to test the versatility of a new basal cell culture medium, GTSF-2. In addition to traditional growth-factors, GTSF-2 contains a blend of three sugars (glucose, galactose, and fructose) at their physiological levels. For these studies, we isolated normal endothelial cells from human, bovine, and rat large blood vessels and microvessels. In addition, GTSF-2 was also tested as a replacement for high-glucose-containing medium for PC12 pheochromocytoma cells and for other, transformed cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…The human tumorigenic lung epithelial cell line A549 was obtained from the American Type Culture Collection (CCL-185). A549 cells to be cultured in three dimensions were initially grown in Corning T75 cell culture flasks containing GTSF-2 (HyClone) (22) supplemented with 10% fetal bovine serum and 100 g of penicillin-streptomycin (Invitrogen) per ml at 37°C in 5% CO 2 before being seeded into the RWV bioreactor. On reaching 75% confluency, the A549 cells were washed with phosphate-buffered saline (PBS) and then removed from the flask by the addition of 0.25% trypsin and washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The human tumorigenic lung epithelial cell line A549 was obtained from the American Type Culture Collection (CCL-185). A549 cells to be cultured in three dimensions were initially grown in Corning T75 cell culture flasks containing GTSF-2 (HyClone) (22) supplemented with 10% fetal bovine serum and 100 g of penicillin-streptomycin (Invitrogen) per ml at 37°C in 5% CO 2 before being seeded into the RWV bioreactor. On reaching 75% confluency, the A549 cells were washed with phosphate-buffered saline (PBS) and then removed from the flask by the addition of 0.25% trypsin and washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Human prostate cancer cells DU 145 (HTB 81) were purchased from American Type Culture Collection (Manassas, VA), and cultures were propagated at 37ÂșC, 5% CO 2 and 95% relative humidity in GTSF-2 complete medium [13] containing 7% fetal bovine serum (pH 7.4). Stock cultures of this cell line were maintained in T-flask and subcultured by trypsinization.…”
Section: Cell Culturementioning
confidence: 99%
“…The cell culture media used included Dulbecco's modified Eagle's medium (DMEM) (Gibco), RPMI-1640 (Gibco), and GTSF-2 medium consisting of triple-sugar minimal essential medium ␣-L-15 base supplemented with 2.2 g/liter NaHCO 3 and 2.5 mg/liter insulin-transferrin-sodium selenite (40).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…At different steps of infection, the pathogen has to acquire nutrients that are necessary for its growth and survival. In this study, we evaluated the in vitro growth of bacteria in both bacterial culture media and cell culture media that are designed to maintain cells under the conditions found in the original tissue (40). The results of this study showed that plasmid-containing derivatives of APEC 7122 grow differently in the different media tested.…”
Section: Vol 78 2010 Role Of Multiple Plasmids In Virulence Of Apecmentioning
confidence: 99%